Whole blood gene expression analysis of spontaneous hypertriglyceridemia in dogs suggests an underlying pro-thrombotic process. - Lauren A Baker; Katie M Minor; Nicole Tate; Eva Furrow (PLoS ONE)
Hypertriglyceridemia (HTG) is influenced by multiple genetic and environmental factors. Spontaneous, idiopathic HTG is common in the Miniature Schnauzer dog and presumed to have a strong genetic influence in this breed. To define genes that are differentially expressed in dogs with HTG, we performed RNA sequencing on peripheral blood of 13 Miniature Schnauzers with HTG and 18 controls. We identified 110 differentially expressed genes (DEGs). Pathway analysis suggests an ongoing pro-thrombotic, endothelial activation process in dogs with HTG. The gene with the largest fold change (5.4 ± 1.4, Padj = 4.4E-04), SERPINE1, encodes plasminogen activator inhibitor 1 (PAI-1), a known risk factor for atherosclerosis and thrombosis. Other top DEGs, including SHANK3, MMRN1, and FZD7, are involved in endothelial activation. Two of the top DEGs, ARHGAP29 and ARHGAP21, inhibit pro-thrombotic pathways and are potentially protective of disease sequelae. Top DEGs, including SERPINE1 and ARHGAP21, have also been linked to metabolic syndrome or its features (e.g. insulin resistance) in humans and animal models. Our findings indicate that HTG in the Miniature Schnauzer dog has similar features to HTG and metabolic syndrome in humans, highlighting the potential use of the dog as a spontaneous model for further research into the etiology and effects of HTG.